High-Fat Diet–Induced Morphometric Alterations in the Rat Salivary Glands - Prasitsak, Thanit; Boonmakum, Komkrith; Tiptirapong, Kanyanut; Tungjai, Pokpong Ritkajorn; Rassaiyakarn, Panuwat; Chinda, Kroekkiat; Sitthikhankaew, Aubonwan; Kreungnium, Siriporn; Sang-Ngoen, Thanyaporn (European Journal of Dentistry, 2025)
High-fat diet (HFD) consumption induces metabolic diseases, which lead to salivary gland alteration. However, the alteration in salivary gland remains inconclusive, and the potential protective effect of simvastatin is limited. Therefore, our study aimed to investigate the effect of HFD consumption and the protective effect of simvastatin on submandibular and sublingual glands in rats.Eighteen male Wistar rats were divided into three groups (n = 6 per group): a control group (C) fed a standard diet, a HFD group (H), and a HFD with simvastatin group (S). After 12 weeks, blood was collected for lipid parameter analysis. Submandibular and sublingual glands were stained with hematoxylin and eosin (H&E), Masson's trichrome, periodic acid–Schiff, and alcian blue to evaluate gland architecture, fibrosis, and mucin content. Image analysis was done using imageJ software.Parametric data were analyzed using one-way ANOVA followed by Tukey's post hoc test. Nonparametric data were analyzed using the Kruskal–Wallis test, followed by Dunn's test. A p-value <0.05 was considered statistically significant.The low-density lipoprotein cholesterol (LDL-C) level significantly increases in the H group compared with the C group (p = 0.004). Acinar cells in both submandibular and sublingual glands were significantly smaller in the H and S groups compared with the C group (p < 0.05). Vacuole-like clear structures were more frequent in the H group. Collagen deposition in the submandibular gland was significantly higher in the H and S groups compared with controls (p = 0.005 and p = 0.011, respectively). Slightly altered mucin staining is seen in both glands.HFD increased LDL-C levels and induced acinar atrophy and fibrosis in the submandibular and sublingual glands. Simvastatin did not protect against salivary gland damage from HFD consumption.
Keywords: dyslipidemia; cholesterol; salivary glands; fibrosis; image analysis; simvastatin